Spine Patient Satisfaction With Telemedicine During the COVID-19 Pandemic: A Cross-Sectional Study. Issue 5 (June 2022) - Satin, Alexander M.; Shenoy, Kartik; Sheha, Evan D.; Basques, Bryce; Schroeder, Gregory D.; Vaccaro, Alexander R.; Lieberman, Isador H.; Guyer, Richard D.; Derman, Peter B.
Study Design: Original research, cross-sectional study. Objectives: Evaluate patient satisfaction with spine care delivered via telemedicine. Identify patient- and visit-based factors associated with increased satisfaction and visit preference. Methods: Telemedicine visits with a spine surgeon at 2 practices in the United States between March and May 2020 were eligible for inclusion in the study. Patients were sent an electronic survey recording overall satisfaction, technical or clinical issues encountered, and preference for a telemedicine versus an in-person visit. Factors associated with poor satisfaction and preference of telemedicine over an in-person visit were identified using multivariate logistic regression. Results: A total of 772 responses were collected. Overall, 87.7% of patients were satisfied with their telemedicine visit and 45% indicated a preference for a telemedicine visit over an in-person visit if given the option. Patients with technical or clinical issues were significantly less likely to achieve 5 out of 5 satisfaction scores and were significantly more likely to prefer an in-person visit. Patients who live less than 5 miles from their surgeon's office and patients older than 60 years were also significantly more likely to prefer in-person visits. Conclusions: Spine telemedicine visits during the COVID-19 pandemic were associated with high patient satisfaction. Additionally, 45% of respondents indicated a preference for telemedicine versus an in-patient visit in the future. In light of these findings, telemedicine for spine care may be a preferable option for a subset of patients into the future.